Internationalisation of research work in library and information field - G. V. Varganova (Библиосфера)
The problems of internationalization of research work (R & D) in the library and information field are considered. Characteristics of the organizational forms of research internationalization are goven. Emphasized is the importance of creating the consortium of domestic and foreign universities, which has created library and information departments, as an organizational form of educational and scientific activities internationalization.